EFEKTIFITAS BERCERITA MENGGUNAKAN MEDIA CANVA UNTUK MENINGKATKAN KEMAMPUAN BERBICARA ANAK DI TK AL MATHOLI TUNAHAN JEPARA - Solekah; Ida Dwijayanti; Sumarno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is a qualitative descriptive study which aims to measure the effectiveness of using Canva media in storytelling activities as a method for improving the speaking skills of PAUD children. The research method used was an experiment with a one group pre-test and post-test design. Data collection uses observation guidelines that have been created by calculating frequencies. The aspect observed is the ability to understand language and express language. Based on the frequency distribution of children's language development, it was found that the increase in children whose speaking skills were still lacking in the BB and MB graphs was 58.33%, decreasing to 37.5%. The results of the research showed that children who were given stimulus by giving stories by teachers using Canva media experienced significant improvements in their speaking skills.